2023
DOI: 10.5194/amt-2023-46
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

POMINO-GEMS: A Research Product for Tropospheric NO2 Columns from Geostationary Environment Monitoring Spectrometer

Abstract: Abstract. Nitrogen dioxide (NO2) is a major air pollutant. Tropospheric NO2 vertical column densities (VCDs) retrieved from sun-synchronous satellite instruments have provided abundant NO2 data for environmental studies, but such data are limited by insufficient temporal sampling (e.g., once a day). The Geostationary Environment Monitoring Spectrometer (GEMS) launched in February 2020 monitors NO2 at an unprecedented high temporal resolution. Here we present a research product for tropospheric NO2 VCDs, referr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…The AD and RD depend on the tropospheric NO 2 abundance, and their monthly variations show a reverse phase of that of the tropospheric NO 2 VCDs (Figure 2). Similarly, previous studies for urban, suburban, rural and remote stations found apparent station dependence, i.e., usually negative deviations in the unban condition and positive deviations in the remote condition for satellite tropospheric NO 2 products [14]. The possible reasons for our finding are:…”
Section: Comparison With the Tropomi And Gems Productssupporting
confidence: 86%
See 4 more Smart Citations
“…The AD and RD depend on the tropospheric NO 2 abundance, and their monthly variations show a reverse phase of that of the tropospheric NO 2 VCDs (Figure 2). Similarly, previous studies for urban, suburban, rural and remote stations found apparent station dependence, i.e., usually negative deviations in the unban condition and positive deviations in the remote condition for satellite tropospheric NO 2 products [14]. The possible reasons for our finding are:…”
Section: Comparison With the Tropomi And Gems Productssupporting
confidence: 86%
“…The AD and RD depend on the tropospheric NO2 abundance, and their monthly variations show a reverse phase of that of the tropospheric NO2 VCDs (Figure 2). Similarly, previous studies for urban, suburban, rural and remote stations found apparent station dependence, i.e., usually negative deviations in the unban condition and positive deviations in the remote condition for satellite tropospheric NO2 products [14]. The possible reasons for our finding are: (1) the ground-based MAX-DOAS is more sensitive to the NO2 in the lower troposphere, while the satellite s sensitivity is higher in the upper troposphere; (2) the layer of high NO2 concentration was close to the surface in the normal urban condition, but the relative NO2 profile had its maximum at higher altitudes during the lockdown period in Lhasa.…”
Section: Comparison With the Tropomi And Gems Productssupporting
confidence: 80%
See 3 more Smart Citations